Relationship between dietary antioxidants and hypertension with the role of genetic factors: a scoping review protocol - Tao Liu; Jianwei Zeng; Miao Huang; Ru Fu; Xiaogang Li; Weihong Jiang (Systematic Reviews)
Abstract Background Hypertension is one of the most common cardiovascular diseases and is responsible for numerous premature deaths worldwide. Antihypertensive drugs cannot fully achieve both effective blood pressure reduction and sufficient protection of target organs. Oxidative stress is considered a critical factor in the development of hypertension. Diet plays a crucial role in hypertension management due to its routine and non-pharmacological nature, and dietary natural antioxidants are believed to play a role in reducing oxidative stress. To date, no reviews have synthesized the evidence on the relationship between total dietary antioxidant capacity and hypertension, its associated target organ damage, and mortality risk, particularly in the context of genetic factors influencing this relationship. This scoping review aims to fill this gap. Methods A systematic search will be conducted across five databases, namely PubMed, Embase, the Cochrane Library, EBSCO, and Web of Science, and gray literature sources for papers published, in line with established scoping review frameworks. The search will cover all relevant studies published up to the date of search initiation. The data will be charted and extracted based on the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews. We will conduct a narrative synthesis in alignment with the stated research questions. Discussion Developing a tailored approach to incorporate dietary antioxidants in hypertension research is crucial for both the scientific community and individuals at risk. Systematic review registration The scoping review protocol has been registered on the Open Science Framework https://doi.org/10.17605/OSF.IO/A6D4M .